Reproductive pattern of Southern geoduck, Panopea abbreviata , at El Sótano (San Matías Gulf, Patagonia, Argentina) - Zaidman, Paula Cecilia (2012)
The reproductive cycle of the southern geoduck (Panopea abbreviata) in a northern Patagonian population was studied throughout a 24-month period (April 2006April 2008) using standard histological techniques and quantitative indicators(oocyte diameter distribution, oocytes per ocular field and relative oocyte area). P. abbreviata exhibits a reproductive pattern characterized, in both sexes, by a continuous proliferation and spawning throughout the year. This is similar to that described in southern geoduck populations and is unique to this genus. Quantitative indicators allowed us to elucidate a slight seasonality in the reproductive cycle: a more pronounced spawning during warm months and gamete accumulation during could months. This article describes the first record of hermaphroditic individuals (n 4) for P. abbreviata.